LANDASAN PENYUSUNAN PROGRAM PEMBELAJARAN MATEMATIKA BAGI SISWA TUNAGRAHITA RINGAN - Dela Devita; Dwi Desmayanasari (Hipotenusa Journal of Research Mathematics Education (HJRME), 2021)
Mentally retarded children or also called children with intellectual disability are children with below average intelligence who experience obstacles in adaptive behavior in the form of taking care of themselves and carrying out activities of daily living. Children with intellectual disability need special education and services to help them achieve optimal development. Children with mild intellectual disability require three basic skills, such as reading, speaking and arithmetic. The implementation of learning in the classroom, especially in learning mathematics requires learning modifications, so that they are in accordance with the individual conditions of intellectual disability students. Intellectual disability students have obstacles to think about something abstract, so in the preparation of learning programs the teacher is expected to; (1) understanding the characteristics of mild intellectual disability students, (2) conducting assessments, (3) being creative in modifying learning methods.